2014
DOI: 10.1186/s13049-014-0051-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, morbidity and mortality from fall-related injuries in the United Arab Emirates

Abstract: BackgroundUnintentional falls are a major cause of morbidity and mortality with a significant burden on victims, families, and societies. We aimed to study the mechanism, risk factors, and outcome of hospitalized patients with fall-related injuries in order to propose preventive measures.MethodsFall-related injured patients who were admitted to Al Ain Hospital, United Arab Emirates (UAE) for more than 24 hours or who died after arrival to the hospital, were studied over 3 years. Demography, location and time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 24 publications
6
20
1
1
Order By: Relevance
“…In the present study, it was revealed that home as a scene of crime was more common in females, while male falling from height was common in work place. This was in accordance with the study carried out by Grivna et al (2014) revealing that the highest risk for falls for UAE nationals and females was at home, while work related falls were more for expatriate males. In contrast Kent and Pearce (2006) found that in Australia, male predominance (91%) was seen in falls both at work and at home.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, it was revealed that home as a scene of crime was more common in females, while male falling from height was common in work place. This was in accordance with the study carried out by Grivna et al (2014) revealing that the highest risk for falls for UAE nationals and females was at home, while work related falls were more for expatriate males. In contrast Kent and Pearce (2006) found that in Australia, male predominance (91%) was seen in falls both at work and at home.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the most affected body region was the extremities (in 90% of the studied cases), followed by the head & neck (in 46.5%), the chest (in 34.5%) then the abdomen (in 16%) and the least affected region was the pelvis (in 11.5%) of course after taking in consideration the overlapping frequencies. Similar results were reported by Grivna, et al, (2014) who found that the most common injured anatomical regions were the extremities (70%), followed by the head& neck (18%), spine (13%), chest (13%) and abdomen (4%). On the other hand, these results disagreed with Icer, et al, (2013) who reported that the most affected body part was the head (in 26.4% of cases), followed by extremities (in 26.2%), then abdomen (in 14.9%) and the least affected was the chest (in 5.3%).…”
Section: Discussionsupporting
confidence: 87%
“…Fall injuries were common in the younger age group of 25–44 mostly related to work or travel followed by 0–14 and predominantly among males similar to another study by Grivna et al (Grivna et al 2014). On the contrary, previous studies have shown that falls were a significant cause of both death and injury in women and older adults in high income countries and in India as well (Cardona et al 2008).…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, majority of the falls occurred at home as against workplace in other studies (Cardona et al 2008; Grivna et al 2014; Tuma et al 2013; Ng et al 2010). The high rates of falls in younger males at home indicate the high level of risk encountered by men and older children in rural India as they go about their usual household and playful activites.…”
Section: Discussionsupporting
confidence: 66%